2022
DOI: 10.24252/jft.v9i1.28815
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Sifat Optik Nanopartikel Karbon (Carbon Dots) Dengan Metode Uv-Vis DRS (Ultraviolet-Visible Diffuse Reflectance Spectroscopy)

Abstract: Research on the synthesis of Carbon Dots using the laser ablation method has been carried out at a time duration of 1, 2, and 3 hours (energy 60 mJ, wavelength 1064 nm and frequency 10 Hz). This research uses organic material from Tea and Toluene as the carbon solvent. The characterization method uses a UV-Vis Diffuse Reflectance Spectroscopy (UV-Vis DRS) spectrum to measure the reflectance value and uses the Kubelka-Munk equation to determine the relationship between the absorbance coefficient parameter (s) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…The smaller the energy band gap (between the conduction band and the valence band), the easier it is for electrons on the valentine band to jump into the conductive band [22]. The smaller the energy band gap (between the conduction band and the valence band), the easier it is for electrons on the valentine band to jump into the conductive band [20]. Given that the overlapping tape is caused by recombination of electrons and holes across the conduction and valence tapes (band gap) and the emission of shallow surface traps due to oxygen vacuum trap (Vo) conditions, it was concluded that the energy of the gap generated for each change was within the energy gap range of semiconductor materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller the energy band gap (between the conduction band and the valence band), the easier it is for electrons on the valentine band to jump into the conductive band [22]. The smaller the energy band gap (between the conduction band and the valence band), the easier it is for electrons on the valentine band to jump into the conductive band [20]. Given that the overlapping tape is caused by recombination of electrons and holes across the conduction and valence tapes (band gap) and the emission of shallow surface traps due to oxygen vacuum trap (Vo) conditions, it was concluded that the energy of the gap generated for each change was within the energy gap range of semiconductor materials.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to know that the formula for the physical characterization of this tool is absorbance, reflectance, transmittance, and energy (bandgap) for this data processing. Band gap energy calculation using UV-Vis Diffuse Reflectance The UV-Vis Diffuse Reflectance spectrophotometric approach is used to generate spectroscopy [20]. The calculated reflectance is the value given in the equation ( 2), and it is used to calculate the Kubelka-Munk equation (equation 3).…”
Section: Methodsmentioning
confidence: 99%